The illustrated dinosaur dictionary - Sattler, Helen Roney (New York : Lothrop, Lee & Shepard Books, 1983)
A dictionary with entries for all known dinosaurs, about 300 at last count, and other animals of the Mesozoic Era, as well as general topics relating to dinosaurs, from Acanthopholis to Zigongosaurus.
Includes bibliographical references and index.
Keywords: Dinosaurs -- Dictionaries; Dinosaurs -- Dictionaries; Extinct animals -- Dictionaries